Multiple hamartomas of the oral cavity with bifid tongue and cleft palate: A unique observation - Moaied Hassan (EL-Med-Pub, 2022)
Background: Hamartomas are developmental tumor-like malformations, comprising a mixture of cytologically mature tissues that are indigenous to their anatomical location.  Within the oral cavity, these lesions are usually multifocal, relatively small, and asymptomatic, and have been frequently linked to present as a manifestation of the oro-facial-digital-syndrome. Case Presentation: A 2-day-old female newborn was referred with two masses protruding from the oral cavity, feeding difficulties, and dribbling of milk during feeding. The patient had no dysmorphic features and no obvious associated anomalies. On careful examination, there was one mass protruding from the undersurface of a bifid tongue with another larger mass that seemed to originate from the hard palate. Complete surgical excision of both masses and repair of the bifid tongue were done to relieve the baby's feeding difficulties. Histopathological examination of both specimens confirmed the diagnosis of multiple hamartomas. Conclusion: The occurrence of multiple and large oral hamartomas in newborns might result in feeding difficulties that necessitate urgent surgical intervention. The association of lingual and palatal hamartomas, with bifid tongue and cleft palate, is a unique observation that is not reported in the English literature.